Recent Advances in Organocatalysis - Karame, Iyad; Srour, Hassan (IntechOpen, 2016)
Organocatalysis has recently attracted enormous attention as green and sustainable catalysis. It was realized as a fundamental field providing wide families of catalysts for important organic transformations. It will certainly develop in the future. Given the diversity of accessible transformations, metal-catalyzed reactions have become major tools in organic synthesis that will undoubtedly continue to have an important impact in the future. Alternatively, over the last years, a metal-free approach such as organocatalysis has reached a level of faithfulness, allowing researchers to discover new catalytic systems based on engagement of new or early-prepared organic molecules as organocatalysts. Organocatalysis meets green chemistry principles, especially the reduction of toxicity and chemical accidents, the biodegradability, and the use of benign and friendlier reaction media and conditions.